NOLEN-SCHIFFER ANOMALY AND RHO(0)-OMEGA MIXING - Krein, G. (Physical Soc Republic China, 1994)
The Nolen-Schiffer anomaly is the long standing discrepancy between theory and experiment of binding energy differences of mirror nuclei. It appears that the anomaly is largely explained by the charge symmetry breaking force generated by the rho(0)-omega mixing. In this paper I discuss the effect of the rho(0)-omega mixing to the binding energy differences in relativistic models of the nucleus. I also discuss the issue of momentum dependence of rho(0)-omega mixing amplitude and present an alternative explanation of the anomaly based on the partial restoration of chiral symmetry in the nucleus.